Late modern ambiguity and gothic narratives of justice - Sothcott, Keir (Critical criminology, 2016)
This paper develops a Cultural Criminology of the Late Modern Gothic. It discusses how representations of criminal justice today are often framed by and narrated through a Gothic imagination. Often, and especially by those who have already noted its criminological significance, this trend is considered a cultural support for Punitive Populism and the demand for vindictive sanctions especially against ‘sensational’ offenders. Although such interpretations are partially valid they do not fully address the entire scope of the Late Modern Gothic—especially when it is invoked as a cultural support for transgression or resistance against the situated structures of (Late) Modernity. By discussing a number of recent media representations but particularly an episode from a popular TV serial, the paper indicates that the contemporary Gothic is now as much a source of subjective identification as it is an imagination of the cultural other: an identification with and not just against that which transcends cultural borders and the culturally ambiguous. Cultural Criminology is here employed to question assumptions that the ‘public mind’ is uniformly punitive and unable or unwilling to tolerate any form of criminal transgression. In responding to popular demands framed by the Gothic imagination, formal criminal justice interventions need not, therefore, necessarily assume a vindictive tone. A Humanistic Cultural Criminological approach to Late Modern Gothic transgressiveness can help reveal cultural complexities too easily ignored by conventional models of criminological analysis.